Effect of surface geometry on low-velocity impact behavior of laminated aramid-reinforced polyester composite - GÜLLÜOĞLU, ARİF NİHAT; EKİCİ, BÜLENT (SAGE PUBLICATIONS LTD, 2016)
The aim of this study is to investigate the effect of surface geometry for low-velocity impact applications. To achieve this purpose, aramid fiber-reinforced laminated polyester composite with various geometries such as cylindrical, elliptical, and spherical were prepared, and low-velocity impact properties were investigated numerically and experimentally. All properties such as orientation, fiber volume fraction, matrix material, and average thickness are the same in all samples. Experimental low-velocity impact behaviors of structure were determined by drop weight tester at low velocity 2.012 m/s. Simulations were carried out by LS-Prepost 4.2 and LS-Dyna v971 software. By this way, results of impact tests were verified and modeled with finite element method. Results of the impact tests showed that the elliptical samples have the highest energy absorption capability due to effective stress transfer capacity. According to experimental results, maximum energy absorption rate difference is 17% between elliptical 10mm and cylindrical 5mm geometries.
Keywords: Polymer matrix composites; impact behavior; numerical analysis; mechanical testing; hand lay-up method; ENERGY-ABSORPTION; SIMULATION; PLATES; PANELS; TESTS; GFRP